The body as archive and memory: a study of fishermen (2024)
This work analyzes one of the important roles of the body which is to conserve or memorialize, to keep practices for future references and use. Using the qualitative research method and participant's observation as tools, this paper explains the importance of dance in human society, that is, the social function of dance as a human activity. Although most people see dance as what everyone can do, dance in the real sense goes beyond bodily movements that human beings engage in every day. This research looks at two selected Nigerian dances: Fishermen and Ikede dances as they embody some specific cultural practices without neglecting the fact that culture is not static. The Ikede dance is a traditional dance of the Ebira people of Kogi State which portrays the art of local weaving. Although it is created and performed within Ebira context, it is a practice that is common to some other people in Nigeria like the Tiv, Egons, and Yorubas etc. These two dances form the basis of analysis in this study. The analysis is based on the performance of these dances by the Kogi State Troupe.